Alternatif Pengoptimalisasian Masa Pakai Tempat Pemrosesan Akhir Di Kota Bandar Lampung - Ali, Nabilah Afriyani; Putri, Husna Tiara; Tanjung, Adinda Sekar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
The problem of waste piles that occur in Bakung Landfill, Bandar Lampung City is influenced by demographic and geographic factors. This Open Dumping alternative is no longer feasible to be applied in accordance with Law No. 18 of 2008 because no waste management is carried out so that it can shorten the life of the landfill. The land area of Bakung Landfill, which was built at 14 Ha, has now remained at ± 3.2469 Ha. So research is needed to analyze the right waste management alternatives to optimize the service life of Bakung Landfill, Bandar Lampung City by considering cost and service life scenarios. The results showed that the increasing waste generation in Bandar Lampung City is related to demographic and geographic factors, thus affecting the increase in the area of need for Bakung Landfill in Bandar Lampung City. There are 3 alternatives to waste management that can optimize the service life of the landfill, namely the first Sanitary Lanfdill Alternative with a service life of 3.6 years, second Alternative Waste to Energy method Refuse Derived Fuel with a service life of 6 years and third Alternative Waste to Energy Incineration method with a service life of >10 years.